Nuclear MBL-1 modulates mitochondrial morphology through carnitine palmitoyltransferase in Caenorhabditis elegans with toxic trinucleotide repeats - Joana Teixeira; Mikko J. Frilander; Ove Eriksson; Susana M. D. A. Garcia (Proceedings of the National Academy of Sciences, 2026)
Expansion of nucleotide repeat sequences is linked to a growing number of neuromuscular degenerative disorders. Metabolic changes, including disruptions in mitochondrial function and dynamics, characterize these disorders and are believed to contribute to organismal toxicity. To investigate how toxic RNA repeats affect mitochondria, we used a Caenorhabditis elegans model that expresses expanded CUG repeat RNAs in muscle cells and recapitulates muscle dysfunction. We found that the RNA-binding protein Muscleblind-like 1 (MBL-1) is essential for normal mitochondrial function and regulates organelle morphology. In animals expressing expanded CUG repeats, where MBL-1 function is impaired, we identified two distinct mechanisms of mitochondrial disruption: altered mitochondrial morphology regulated by MBL-1, and oxidative phosphorylation (OxPhos) dysfunction occurring independently of MBL-1. Our data further show that changes in mitochondrial morphology are specifically linked to nuclear MBL-1 dysfunction, which affects cpt-3 expression, a gene encoding carnitine palmitoyltransferase—an enzyme required for fatty acid transport into mitochondria. This mechanism is conserved, with similar disruptions observed in patients with Myotonic Dystrophy type 1. Importantly, our findings indicate that increased organelle fragmentation is not central to cellular pathogenesis. Instead, OxPhos dysfunction appears to be a primary contributor to organismal toxicity.